Halal Certification System As A Resource For Firm Internationalisation: Comparison Of China And Malaysia - N. Dubé, François; Hongxia, Zhao; Haijuan, Yang; Lijun, Huang (Penerbit Universiti Sains Malaysia (USM Press), 2016)
There is a broad consensus to the effect that public agencies can mitigate the obstacles and uncertainties associated with the process of firm internationalisation. One critical aspect of such interventionist policy is the establishment of a national/regional halal certification system, which has been widely recognised as a core factor in the international expansion of halal food firms. Based on thorough field research conducted in the halal food industries of the Ningxia Autonomous Hui Region of China and Malaysia, the present article examines how different models of halal certification can promote and ease access of local firms to international markets. Using both qualitative and quantitative methodologies, the present article allows the authors to formulate general conclusions on the relationship between firm internationalisation and halal certification, as well as specific insights for halal food industries elsewhere seeking to promote their international activities.